ANALISIS PREFERENSI DAN PENGAMBILAN KEPUTUSAN KONSUMEN DALAM PEMBELIAN PRODUK OLAHAN SEAFOOD (STUDI KASUS DI KOTA BANDUNG PROVINSI JAWA BARAT) - Atikah Nurhayati; Ayi Yustiati; Asep Agus Handaka (Universitas Pattimura, 2020)
Bandung City is one of the regions in West Java Province that has culinary tourism potential, one of which is processed seafood culinary products. Seafood is one source of animal protein that is widely consumed by the wider community. Processed seafood products have many variations of flavors with prices that are relatively affordable by consumers. This research aims to analyze consumer preferences and decision making in purchasing processed seafood products. The method used in this research is survey. Conducting research in March - July 2019 in the city of Bandung. Primary and secondary data used. Primary data collection techniques using purposive sampling while secondary data obtained from the Central Statistics Agency Bandung City Office. To analyze consumer preferences used attitude measurement analysis as measured by a Likert Scale. Multiple linear regression analysis is used to analyze which attributes are most considered in the selection of processed seafood products. Based on the results of research preferences and consumer decision making in the purchase of processed seafood products are the taste of processed seafood products, the nutritional content of processed seafood products, the location and facilities of processed seafood products and the prices of processed seafood products.